2018
DOI: 10.21817/ijet/2018/v10i4/181004216
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphy and Microfacies of Qom Formation in Urumieh – Dokhtar Zone, Iran

Abstract: Qom Formation is well developed in Urumieh-Dokhtar Zone, Iran. Three different measured sections were studied in this area in order to interpret the biostratigraphy and microfacies of QomFormation. In the Ashtian and Hezar Abad sections, the Qom Formation disconformably overlies and underlies Lower Red and Upper Red formations, respectively.In the Rakin section, the lower boundary of Qom Formation with tuffs of Urumieh-Dokhtar magmatic arc is sharp and its upper boundary is covered by the recent alluvium. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In our study, participants in different cities and from different social backgrounds reported watching, listening to, and reading pop-psychology lectures given by Iranian psychologists in the diaspora (such as radio and TV shows by Dr. Holakouee 4 and Dr. Farnoody 5 ) as well as reading selfhelp lessons (mostly through social media and satellite TV programs) as common pathways to understand their psychological and interpersonal difficulties and obtain advice. In their live audio and video programs (both in recorded and online format), Iranian psychologists in the diaspora respond to people's questions about their relational challenges, including marital and family problems, using psychological techniques drawing from systemic, cognitivebehavioral therapies, as well as acceptance and commitment therapy.…”
Section: Alternative Pathways To Carementioning
confidence: 99%
“…In our study, participants in different cities and from different social backgrounds reported watching, listening to, and reading pop-psychology lectures given by Iranian psychologists in the diaspora (such as radio and TV shows by Dr. Holakouee 4 and Dr. Farnoody 5 ) as well as reading selfhelp lessons (mostly through social media and satellite TV programs) as common pathways to understand their psychological and interpersonal difficulties and obtain advice. In their live audio and video programs (both in recorded and online format), Iranian psychologists in the diaspora respond to people's questions about their relational challenges, including marital and family problems, using psychological techniques drawing from systemic, cognitivebehavioral therapies, as well as acceptance and commitment therapy.…”
Section: Alternative Pathways To Carementioning
confidence: 99%